Xylanolytic complex from Aspergillus giganteus: production and characterization - Coelho, G. D.; Carmona, E. C. (Wiley-Blackwell, 2003)
An Aspergillus giganteus strain was isolated as an excellent producer of xylanase associated with low levels of cellulase. Optimal xylanase production was obtained in liquid VOGEL medium containing xylan as carbon source, pH 6.5 to 7.0, at 25degreesC and. under shaking at 120 rpm during 84h. Among the several carbon sources tested, higher xylanase production was verified in xylan, xylose, sugar-cane bagasse, wheat bran and corn cob cultures, respectively. Optimal conditions for activity determination were 50degreesC and pH 6.0. The xylanolytic complex of A. giganteus showed low thermal stability with T-50 of 2 h, 13 min and I min when it was incubated at 40, 50 and 60degreesC, respectively, and high stability from pH 4.5 to 10.5, with the best interval between 7.0 to 7.5. This broad range of stability in alkali pH indicates a potential applicability in some industrial processes, which require such condition. Xylanolytic activity of A. giganteus was totally inhibited by Hg+2, Cu+2 and SDS at 10 mm. The analysis of the products from the oat spelts xylan hydrolysis through thin-layer chromatography indicated endoxylanase activity, lack of debranching enzymes and P-xylosidase activity in assay conditions.